2013
DOI: 10.1007/s13760-013-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of C-reactive protein for early mortality after ischemic stroke: comparison with NIHSS score

Abstract: We aimed to compare the association of high-sensitivity C-reactive protein (CRP) and National Institutes of Health Stroke Scale (NIHSS) score with mortality risk and to determine the optimal threshold of CRP for prediction of mortality in ischemic-stroke patients. A series of 162 patients with first-ever ischemic-stroke admitted within 24 h after onset of symptoms was enrolled. CRP and NIHSS score were estimated on admission and their predictive abilities for mortality at 7 days were determined by logistic-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…In particular, CRP levels >2.2 mg/L were found to be associated with high mortality in these cases. 9 However, in the current study, there was no statistically significant difference between the mortality and discharged groups in terms of CRP levels even though the former group had a relatively higher CRP value )p=0.48(. Previous studies reported that the area of ischemic infarct presenting with restricted diffusion in diffusion-weighted MR imaging is important for the prediction of some neurological deficits as well as for prognosis.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…In particular, CRP levels >2.2 mg/L were found to be associated with high mortality in these cases. 9 However, in the current study, there was no statistically significant difference between the mortality and discharged groups in terms of CRP levels even though the former group had a relatively higher CRP value )p=0.48(. Previous studies reported that the area of ischemic infarct presenting with restricted diffusion in diffusion-weighted MR imaging is important for the prediction of some neurological deficits as well as for prognosis.…”
contrasting
confidence: 63%
“…Ghabaee et al 9 reported that CRP value and NIHSS score had a high sensitivity for mortality prediction in stroke cases. In particular, CRP levels >2.2 mg/L were found to be associated with high mortality in these cases.…”
mentioning
confidence: 99%
“…This hypothesis has been observed in several clinical studies, with the high levels of serum Hcy as independent predictors for END for stroke patients [11, 14]. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15].…”
Section: Discussionmentioning
confidence: 83%
“…The serum Hcy levels were found to be significantly higher in stroke patients than those of normal controls [11-13]. Also, the high levels of serum Hcy were independent predictors for early neurological deterioration (END) and death in multivariate analysis [14], with the prognostic accuracy of 0.83 and 0.82, respectively [11]. These findings suggest that Hcy may be an effective biomarker for early diagnosis and prognosis of lacunar infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Some have shown that only younger age and localized disease (27), tumor diameter less than 25 mm (10), and low-grade histology (5,10,12) were associated with better prognoses and that surgery and adjuvant radiotherapy may not influence overall survival (27), while others have focused on the role of gross total resection, refusing a long-term role for adjuvant therapy (9), both in benign pineocytomas (2,(6)(7)(8)13) and pineoblastomas (28). Some other studies, nonetheless, have shown a beneficial role for adjuvant therapy, either alone (4) or after gross total surgical resection (15,17,22).…”
mentioning
confidence: 99%